Pengaruh reward dan recognition untuk meningkatkan in role dan extra role behavior karyawan yang dimediasi oleh employee engagement di Petrochina International Jabung Ltd - Shadiq, Annurusshadiq; Rosita, Sry; Aurora Lubis, Tona (Jurnal Paradigma Ekonomika, 2022)
The pupose of this study was to examine and determine the effect of reward and recognition to increase in-role and extra-role behavior of employees mediated by employee engagement at Petrochina International Jabung Ltd. – Jambi. The sample used in as many as 81 respondents. Data collection and the method used is a method with a questionnaire that has been tested for validity and reliability then measured using a likert scale and the hypothesis is then analyzed by Structural Equation Modeling (SEM) based on Partial Least Squares Path Modeling (PLS-SEM) components. The results of statistical analysis prove that direct rewards have an insignificant effect on in-role and extra-role behavior and have no significant effect on employee engagement. Recognition directly has an insignificant effect on in-role and extra-role behavior and has a positive and significant effect on employee engagement. The results of statistical analysis also prove that employee engagement has a positive and significant effect on in-role and extra-role behavior. For the mediating effect of the employee engagement variable, it is proven that employee engagement can mediate the indirect influence relationship between recognition on in-role and extra-role behavior.